2013
DOI: 10.1021/ol400539h
|View full text |Cite
|
Sign up to set email alerts
|

Ligand- and Base-Free Pd(II)-Catalyzed Controlled Switching between Oxidative Heck and Conjugate Addition Reactions

Abstract: A simple change of solvent allows controlled and efficient switching between oxidative Heck and conjugate addition reactions on cyclic Michael acceptor substrates, catalyzed by a cationic Pd(II) catalyst system. Both reactions are ligand- and base-free and tolerant of air and moisture, and the controlled switching sheds light on some of the factors which favor one reaction over the other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Within this context, controlled switching between the Pd(II)catalysed oxidative Heck and conjugate addition reactions have recently been reported (Scheme 4). 18,19 A simple change of solvent from DCE (ClCH 2 CH 2 Cl) to DMSO switches the reaction from conjugate addition to oxidative Heck.…”
Section: Oxidative Boron Heck Reactionmentioning
confidence: 99%
“…Within this context, controlled switching between the Pd(II)catalysed oxidative Heck and conjugate addition reactions have recently been reported (Scheme 4). 18,19 A simple change of solvent from DCE (ClCH 2 CH 2 Cl) to DMSO switches the reaction from conjugate addition to oxidative Heck.…”
Section: Oxidative Boron Heck Reactionmentioning
confidence: 99%
“…Several mechanisms for the CH functionalization of BQ are possible. Previously, we showed that the reaction with cyclohexenones under ligand‐free conditions can be switched between oxidative Heck and conjugate addition in the final step of the cycle 19b. Similarly, the CH functionalization of BQ could proceed through 1) a direct Pd II ‐catalyzed oxidative Heck reaction, with the oxidant (BQ or 2,6‐DCBQ) needed to reoxidize Pd 0 to Pd II , or 2) conjugate addition to form functionalized hydroquinone, which is then oxidized in situ to the functionalized BQ product.…”
Section: Methodsmentioning
confidence: 99%
“…In reactions with cyclic olefins as substrates, the selectivity was lower, and two products were formed for cyclohexene-3-on (Table 4, entry 2) and for cyclohexene ( Table 4, entry 4). The saturated ketone, found in the reaction of cyclohexene-3-on, was formed via conjugate addition reaction involving intermediate form in which ketone coordinated to palladium via Pd-O bond [69]. The isomerization of the arylated cycloheptene resulted in the formation of four products in comparable amounts ( Table 4, entry 6).…”
Section: Effect Of Substrates: Olefins and Arylboronic Acidsmentioning
confidence: 99%